Nordic cyanobacterial and algal lipids: Triacylglycerol accumulation, chemotaxonomy and bioindustrial potential - Santana-Sánchez Anita; Lynch Fiona; Sirin Sema; Allahverdiyeva Yagut (Wiley-Blackwell Publishing, Inc., 2022)
The ability to capture and convert sunlight, water and nutrients into useful compounds make photosynthetic microbes ideal candidates for the bio-industrial factories of the future. However, the suitability of isolates from temperate regions to grow under Nordic conditions is questionable. In this work, we explore the chemotaxonomy of Nordic strains of cyanobacteria and one green alga and evaluate their potential as raw materials for the production of lipid-based bio-industrial compounds. Thin-layer chromatography was used to identify the presence of triacylglycerol, which were detected in the majority of strains. Fatty acid methyl ester profiles were analysed to determine the suitability of strains for the production of biodiesel or the production of polyunsaturated fatty acids for the nutraceutical industry. The Nordic Synechococcus strains were unique in demonstrating fatty acid profiles comprised mostly C14:0, C16:0 and C16:1 and lacking polyunsaturated fatty acids. These properties translated to superior predicted biodiesel qualities, including cetane number, cold filter plugging point and oxidative stability compared to the other evaluated strains. Polyunsaturated fatty acids were detected at high levels (38-53%), with Calothrix sp. 336/3 being abundant in two essential fatty acids, linoleic and alpha-linolenic acid (21 and 17%, respectively). Gamma-linoleic acid was the predominant polyunsaturated fatty acid for the remaining strains (13-21%). In addition to assessing the potential of Nordic strains for bio-industrial production, this work also discusses issues such as taxonomy and predictive modelling, which can affect the identification of prospective high-performing strains.